Letter (copy) : Spanish seamen - Tewson, Vincent
025a-0084-001 International HVT/AC/352 15th August, 1939. Señor José I. de Lizaso, Basque Delegation, 14, Eccleston Sq., S.W.1. Dear Señor de Lizaso, SPANISH SEAMEN. You will remember that, when the British Courts gave the Franco Government possession of certain Spanish ships lying in British ports, the authorities granted to the Spanish seamen who were thus left without means of livelihood permission to remain in this country on the understanding that steps would be taken to find them a new home by means of emigration or other settlement. We are aware that discussions are now proceeding for these men to be emigrated, and that they are now making application for inclusion in the general emigration scheme. We have been, and are being, constantly pressed by the Home Office to give them some indication of the date when the plans for the settlement of these men are likely to mature. We have been compelled repeatedly to put off their enquiries, without having, however, either for our own guidance or for the purposes of reassuring the authorities, any definite information as to the stage which the negotiations for the departure of these men have now reached. You will appreciate that we rely very much upon the co-operation of the officials of the Emigration Branch of the Home Office, who are justifiably anxious that an early solution shall be found of this problem. We should therefore be extremely obliged if you could urge the bodies responsible to conclude at as early a date as possible the arrangements for the settlement of these men, and to give you some information as to the date when this can be effected. Our actions have spoken our concern for the future of your homeless countrymen, and I know you will appreciate that we have finally raised the question with you in view of its great importance in the interests of the men. Yours sincerely, Assistant Secretary. 292/946/25a/84